Postoperative wound leak and anterior chamber reaction in patients undergoing phacoemulsification cataract surgery with sutured and sutureless corneal incisions - Sameer Khan, Khabir Ahmad, Tanveer Anjum Chaudhry, M. H. Shahzad (Pakistan Journal of Ophthalmology, 2007)
Purpose: To compare the rates of significant post operative wound leak and anterior chamber (AC) reaction in patients undergoing phacoemulsification cataract surgery with sutured and sutureless corneal incisions. Material and Methods: All eyes scheduled to have phacoemulsification surgery by two surgeons at two centers were selected. The first group of eyes underwent phacoemulsification surgery with 3.25 mm superior and superior-temporal clear corneal incisions. The incision was sutured using a single 10/0 nylon suture. The second group of eyes underwent an identical surgery, but the incision was not sutured. Patients were followed up at 24 hours, and 1 week and evaluated by slit lamp for wound leak (using Seidel's Test) and AC cells and flare. Results: Forty eight eyes underwent surgery with sutured corneal incisions and 50 eyes underwent sutureless surgery. The mean age of patients in groups I and II were 61.2 years and 63.3 years, respectively. Following surgery, none of the patients in two groups showed wound leak at 1 day and 1 week. At the first post-op day, only 14.6% of eyes in group 1 showed AC reaction, compared to 32.0 % in group II (p = 0.04). At one week postop, 16.7% and 20.0% of eyes in Groups I and II showed AC reaction, respectively. However, the difference was not statistically significant (p = 0.67). Conclusions: The rates of postoperative wound leak and anterior chamber reaction in patients undergoing phacoemulsification cataract surgery with sutured and sutureless corneal incisions are not different. Thus sutured surgery offers no added advantages.